Dominant Vortex Structures in Transverse Jets - Bayraktar, S.; Yilmaz, T. (ISFAHAN UNIV TECHNOLOGY, 2016)
In this paper, formation and development of one of the most dominant vortex structures, namely, counter rotating vortex pair (CVP) which is seen in the jet in crossflow are investigated numerically. Influences of the inclination angles between the nozzle(s) and channel on the CVP are presented for three inclination angles, a=30 degrees, 60 degrees and 90 degrees at velocity ratio, R=2.0. Effects of the number of the nozzles on the evolution of CVP is analyzed by considering the single and three side-by-side positioned circular nozzles. In addition to the CVP, some secondary vortices are also reported by considered relatively a narrow channel because their existence cannot be showed in wider channel. Simulations reveal that higher the inclination angle the more jet penetration into the channel in all directions and increasing the inclination angle causes larger CVPs in size. Although the flow structure of the CVP formed in the single and three side-by-side nozzles are similar their evolution is quite different.
Keywords: Transverse jet; Turbulent flow; Counter-rotating vortex pair (CVP); Computational fluid dynamics (CFD); LARGE-EDDY SIMULATION; FILM-COOLING FLOWS; CROSS-FLOW; Thermodynamics; Mechanics